A case study on accelerated light‐ and elevated temperature‐induced degradation testing of commercial multi‐crystalline silicon passivated emitter and rear cell modules. (27th July 2021) - Ciesla, Alison; Kim, Moonyong; Wright, Matthew; Zafirovska, Iskra; Chen, Daniel; Hallam, Brett; Chan, Catherine
Abstract: Light‐ and elevated temperature‐induced degradation (LeTID) can have significant and long‐lasting effects on silicon photovoltaic modules. Its behaviour is complex, showing highly variable degradation under different conditions or due to minor changes in device fabrication. Here, we show the large difference in LeTID kinetics and extents in multi‐crystalline passivated emitter and rear cell (multi‐PERC) modules from four different manufacturers. Varied accelerated testing conditions are found to impact the maximum extent of degradation in different ways for different manufacturers complicating the ability to develop a universal predictive model for field degradation. Relative changes in the open‐circuit voltage ( V OC ) have previously been used to assess extents of LeTID; however, due to the greater impact of the defect at lower injection, the V OC is shown to degrade less than half as much as the voltage at maximum power point ( V MPP ). The MPP current ( I MPP ) and fill factor (FF) also degrade significantly, having an even larger overall impact on the power output. These observations imply that currently employed methodologies for testing LeTID are inadequate, which limits the reliability of future predictive models. In light of this, the field must develop a more holistic approach to analysing LeTID‐impacted modules, which incorporates information about changes under MPP conditions. This will allow for a much clearer understanding of LeTID in the field, which will assist the performance of future PV systems. Abstract : LeTID is shown to vary widely in terms of kinetics and maximum extent in modules from different manufacturers. Accelerated testing procedures can alter the maximum extent of degradation observed with no obvious trend, creating challenges for predicting future power output. The maximum power point voltage ( V MMP ) is found to degrade twice as much as the open‐circuit voltage ( V OC ) and is therefore a better indicator of LeTID. However, all module performance parameters are shown to degrade due to LeTID.